2006
DOI: 10.4049/jimmunol.177.12.8542
|View full text |Cite
|
Sign up to set email alerts
|

CD5-CK2 Binding/Activation-Deficient Mice Are Resistant to Experimental Autoimmune Encephalomyelitis: Protection Is Associated with Diminished Populations of IL-17-Expressing T Cells in the Central Nervous System

Abstract: Regulating the differentiation and persistence of encephalitogenic T cells is critical for the development of experimental autoimmune encephalomyelitis (EAE). We reported recently that CD5 has an engagement-dependent prosurvival activity in T cells that played a direct role in the induction and progression EAE. We predicted that CD5 regulates T cell apoptosis/survival through the activation of CK2, a prosurvival serine/threonine kinase that associates with the receptor. To test this hypothesis, we generated mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 51 publications
5
85
1
Order By: Relevance
“…More specifically, Casein Kinase 2, a serine/threonine kinase that associates with CD5 in thymocytes [37], was shown to play a crucial role in cell survival and apoptosis [61]. In this context, CD5 À/À CD4 1 T cells, as well as CD4 1 T lymphocytes that express a Casein Kinase 2 binding/ activation-deficient CD5, are more susceptible to apoptosis induction than WT CD4 1 T cells [62]. However, the molecular mechanism by which CD5 may prevent thymocyte apoptosis had not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, Casein Kinase 2, a serine/threonine kinase that associates with CD5 in thymocytes [37], was shown to play a crucial role in cell survival and apoptosis [61]. In this context, CD5 À/À CD4 1 T cells, as well as CD4 1 T lymphocytes that express a Casein Kinase 2 binding/ activation-deficient CD5, are more susceptible to apoptosis induction than WT CD4 1 T cells [62]. However, the molecular mechanism by which CD5 may prevent thymocyte apoptosis had not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
“…For suppression assays, CD4 1 CD25 1/hi (Treg) and CD4 1 CD25 À naïve T cells (T effectors, Teff) (1 Â 10 5 ) were incubated at 1:1 ratio in the presence of irradiated splenocytes and stimulated with anti-CD3 antibody. T-cell proliferation was measured by 3 activation-deficient CD5, are more susceptible to apoptosis induction than WT CD4 1 T cells [62]. However, the molecular mechanism by which CD5 may prevent thymocyte apoptosis had not yet been explored.…”
mentioning
confidence: 99%
“…Interestingly, it has been shown that EAE is also more difficult to induce in transgenic mice that express a CD5 molecule deficient in its interaction with casein kinase 2 (48,49). The increased resistance to EAE has been interpreted to be due to reduced survival of effector T cells in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of CD5 are associated with resistance to activation in peripheral T cells and blocking CD5 restores their responsiveness (22). The negative regulatory ability of CD5 has also been shown to play a critical role in preventing hyper-proliferation and activation-induced cell death (AICD) when examining CD8 + T cells in a tumor model and in CD4 + and CD8 + cells in experimental autoimmune encephalomyelitis (23)(24)(25). We find that CD5 does prevent hyperproliferation in LLO56 and possibly AICD at later stages.…”
Section: Discussionmentioning
confidence: 99%